Neural Pathways of Visual Face Recognition Immediately After Birth - Carlo Lai; Chiara Ciacchella; Daniela Altavilla; Giorgio Veneziani; Giuseppe Marano; Gaia Romana Pellicano; Giacomo Della Marca; Federico Tonioni; Paola Aceto; Marco Cecchini; Eugenio Maria Mercuri; Luigi Janiri; et al. (Life)
The present study aimed to investigate the electrophysiological correlates of face-identity recognition in newborn infants immediately after birth. Electroencephalographic acquisition was continuously recorded in 23 newborn infants (3 < age < 24 h of life) during the following visual task: presentation of a woman’s face for 60 s (“known face”); random presentation of 50 known faces, 50 novel women’s faces, and 50 chessboards (for 2 s each). The final sample included in ERP analyses was composed of 11 newborn infants (male/female: 6/5; age: 5 h 16′ ± 3 h 51′). A greater negative amplitude of the N290 and smaller P400 and LC2 were found in response to the known face compared with the novel one in the left hemisphere. A shorter N290 latency was detected during the known face presentation compared with the novel one, and a longer latency of the same component was observed during novel face presentation compared with the chessboard. These findings suggest that newborns process a face differently from an object at birth and that they can discriminate a new face from a familiar one previously viewed for one minute.